Reversal of Roux-en-Y Gastric Bypass: A Multi-Centric Analysis of Indications, Techniques, and Surgical Outcomes - Plath, Liane; Vannijvel, Marie; Okkema, Sietske; Deleus, Ellen; Lloyd, Aaron; Lo Menzo, Emanuele; Tadros, George; Raguz, Ivana; San Martin, Andres; Kraljević, Marko; Mantziari, Styliani; Frey, Sebastien; et al. (Springer Science and Business Media LLC, 2025)
Background
Roux-en-Y gastric bypass may present long-term complications that require revisional surgery or even reversal to normal anatomy. Data on the indications, surgical technique, and outcomes of RYGB reversal remain scarce.
Methods
We identified 48 cases of RYGB reversals with complete 90-day follow-up within a multi-centric international retrospective database of elective secondary bariatric surgery. The operations were performed between 2010 and 2024 in high-volume referral centers in Europe and USA. Data were collected on body weight, associated diseases, and on surgical outcomes up to 1-year postoperatively.
Results
Patients were mainly female (81.3%) with a median age of 50 years (IQR 39–56). RYGB reversal was performed 7 years (median) after primary RYGB in patients with a BMI of 23.9 kg/m2 (IQR 20–27). Half of the patients underwent at least 1 bariatric revision before the reversal. Main indications for reversal were dumping syndrome (33.3%), excessive weight loss (29.2%), marginal ulcer (14.6%), malabsorption (12.5%), and abdominal pain (10.4%). Rate of conversion to open surgery was 8.3%, and the postoperative complications during the first year reached 50%, including 31.3% Clavien-Dindo grade I–II, 16.7% grade III–IV complications, and one death. At 1 year, the mean BMI of the cohort increased by 18% to 28.25 kg/m2; only 1 patient reached pre-RYGB BMI.
Conclusion
Although RYGB is a theoretically reversible procedure, normal anatomy is re-established only in selected cases which are refractory to medical therapy and often also to revisional bariatric surgery. RYGB reversals entail high morbidity, while the extent of recurrent weight gain at 1-year post-reversal seems to allow patients to remain below the threshold of severe obesity.